EFEKTIVITAS PELAYANAN PERIZINAN TERHADAP KINERJA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA BENGKULU - Aprianty, Henny; Arifah, Alia; Alexsander, Alexsander (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
The aim of this research is to find out the effectiveness of licensing services on the performance of the Bengkulu City Investment and One Stop Licensing Service. The population used in this study is the licensing applicant from the Bengkulu City Investment and One-Stop Service Office. The sampling technique uses descriptive qualitative based on predetermined criteria. Data collection techniques in this case are observation, documentation and questionnaires. The results of this study conclude that the effectiveness of licensing services on performance at the Bengkulu City Investment and One Stop Service Service is that the Effectiveness of Licensing Services at the Bengkulu City Investment and One Stop Service Service is still less than 82% or accept H0.